Review of CO2 price in Europe using feed-in tariff rates - Bakhtyar, Bardia; Fudholi, A.; Hassan, Kabir; Azam, Muhammad; Lim, C.H.; Chan, N.W.; Sopian, K. (Elsevier B.V., 2017)
The price of carbon emitted by thermal plants has always been a favorite topic of researchers and policy makers.A substitute price for CO2 is calculated in this study based on real-time payments through government tariffs.These payments aim to mitigate CO2 emission caused by unregulated electricity generation.The total CO2 produced by the thermal plants of 10 European countries is shown in this study.The government's payment for each technology is utilized to clear the final CO2 abatement cost.The substitute price of avoiding CO2 emission (SPAC) for each technology and country is estimated.SPAC is basically the price that each country pays to avoid producing CO2. The conducted survey shows that the SPAC of the 10 European countries ranges from 63 to 2951 Euros depending on the type of technology used and the country's policy.Results confirm a competitive payment by governments only for German and UK hydro and UK wind technologies.Comparison of the countries’ payments for renewable energies and CO2 market price shows that governments incurred an inefficient payment of liquidity as a carbon mitigation policy.